Generalization of One Sufficient Condition for Fourier Multipliers - Kolomoitsev, Yu. S. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We obtain new sufficient conditions for Fourier multipliers in the Hardy spaces $H_p(\mathbb{R}^n),\; 0 < p < 2$. These conditionsare given in terms of the simultaneous behavior of a function and its derivatives. The results of this paper generalize the corresponding theorems of A. Miachi.